Predictive nursing for catheter dislocation in placement of peripheral central venous catheter (经外周静脉置入中心静脉导管脱出的预见性护理) - WANG Nanan (王楠楠); SU Guohua (苏国华); GUO Lian (郭连); WANG Yutao (王玉涛); E Haiyan (鄂海燕); LIU Yunchao (刘云超) (Association of Integrative Nursing, 2021)
Peripherally inserted central venous catheters (PICC), showing advantages of easy-to-operate, safe, minimal invasion, long-term retention and easy-to-maintain, is widely used in transfusion therapy. However, catheter dislocation during placement may lead to unplanned extubation. Causes of catheter dislocation mainly include unstable fixation, inadequate health education and poor patient compliance. The countermeasures of nursing include catheterization and maintenance by professionals, correct way of skin disinfection, selection of right application, appropriate catheter fixation methods, mastery of application replacement measures, and adequate health education. Predictive nursing is a nursing process in which nurses make a comprehensive analysis and diagnosis of patient's condition, predict the potential risks and carry out effective nursing interventions to prevent complications. In order to reduce the risk of catheter dislocation, the key issue of predictive nursing is to enhance the prevention and control of each process. (经外周静脉置入中心静脉导管(PICC)技术具有操作简单、安全、创伤小、保留时间长、易于维护等优点, 被广泛应用于临床。但留置期间一旦出现导管脱出, 会导致非计划性拔管。发生导管脱出的原因主要有固定不牢、健康教育不到位、患者依从性差, 护理对策包括专业人员置管及维护、正确的皮肤消毒方法、选择敷贴、适宜的导管固定方法、掌握敷贴更换方法、做好健康教育等。预见性护理是护士运用护理程序对患者进行全面与综合的分析与判断, 提前预知存在的护理风险, 从而采取及时有效的护理措施, 避免护理并发症的发生, 提高护理质量和患者的满意度。护理重点是预防, 控制好每个环节, 将导管脱出风险降至最低。)